A phylogeny of the enigmatic Madagascan geckos of the genus Uroplatus (Squamata: Gekkonidae) - Greenbaum, Eli; Bauer, Aaron M.; Jackman, Todd R.; Vences, Miguel; Glaw, Frank (Zootaxa, 2007)
Since its discovery in the 17th century, the morphological peculiarities of the gekkonid lizard genus Uroplatus have generated a great deal of attention. A large number of skeletal, integumentary and visceral features are autapomorphic for the genus and some of the more well-known members of the group possess such aberrant characteristics that a separate family was once recognized to accommodate them. Recent phylogenetic analyses confirm that Uroplatus is a typical gekkonid gecko, but the specific affinities of the genus, as well as its intrageneric relationships have remained unresolved. Both nuclear (RAG-1 and PDC) and mitochondrial (ND2 and cyt b) genes (~3.2 Kb) were sequenced for 10 of 13 recognized species of Uroplatus, as well as two Madagascan and mainland African outgroups. The large-bodied forms of Uroplatus (U. fimbriatus, U. giganteus, U. henkeli, and U. sikorae) form a monophyletic group, and the smallbodied, short-tailed species are also monophyletic (U. ebenaui and U. phantasticus). Uroplatus alluaudi + U. pietschmanni comprise another distinct clade, whereas U. lineatus was weakly supported as the sister taxon of the largebodied clade and U. guentheri was sister to all other members of the genus. Our phylogenetic hypothesis based on combined DNA sequence data is mostly congruent with previous hypotheses based on morphological data. Based on a larger, more inclusive dataset, the closest relatives of Uroplatus are mainland African Afrogecko and Madagascan Matoatoa, suggesting that the diverse Malagasy gecko fauna does not comprise a single evolutionary lineage. A high diversity of new taxa (either representing synonyms to resurrect or undescribed species), morphologically similar either to U. ebenaui/phantasticus or to U. henkeli/sikorae, was apparent from our data. Many of these genetically highly divergent lineages originated from localities in northern Madagascar, which indicates this region as the possible center of diversity and endemism for several subgroups of Uroplatus.